Prospects Of Use Of Solar Energy At Drying Of Cocoons - T. Butayev; O‘. Mamajonov (Zien Journals, 2021)
The article describes the prospects for the use of solar energy in the drying of cocoon raw materials.
Keywords: cocoon; collector; valve of adjustment; fan